In or out of control: Modulating regulatory T cell homeostasis and function with immune checkpoint pathways - Abdeladhim, Maha; Karnell, Jodi L.; Rieder, Sadiye Amcaoglu (Frontiers in Immunology, 2022)
Regulatory T cells (Tregs) are the master regulators of immunity and they have been implicated in different disease states such as infection, autoimmunity and cancer. Since their discovery, many studies have focused on understanding Treg development, differentiation, and function. While there are many players in the generation and function of truly suppressive Tregs, the role of checkpoint pathways in these processes have been studied extensively. In this paper, we systematically review the role of different checkpoint pathways in Treg homeostasis and function. We describe how co-stimulatory and co-inhibitory pathways modulate Treg homeostasis and function and highlight data from mouse and human studies. Multiple checkpoint pathways are being targeted in cancer and autoimmunity; therefore, we share insights from the clinic and discuss the effect of experimental and approved therapeutics on Treg biology.